Efeito da inoculação com fungo micorrízico arbuscular e da adubação orgânica no desenvolvimento de mudas de sabiá (Mimosa caesalpiniaefolia Benth.), sob estresse salino - Tavares, Rodrigo de Castro (2007)
Salt affected soils management is an important subject to be studied, especially when irrigated arid and semi-arid regions are considered, as soil salt excess may limit growth and plant productivity. The objective of this dissertation was to evaluate the effect of mycorrhizal arbuscular fungi (AMF) inoculation on growth of sabiá plants (Mimosa caesalpiniaefolia Benth.), cultivated under salt stress in the presence or absence of organic compost. Thus, an experiment was conducted under green-house conditions to evaluate the potential of inoculated and fertilized plant establishment submitted to salt stress, in a complete randomized factorial design 2 (inoculated or non-inoculated plants) X 2 (fertilized or non-fertilized with organic compost) X 5 levels of irrigation water electrical conductivity (0.7, 1.2, 2.2, 3.2 and 4.2 dS m’), with 4 replications. After 60 days from germination, plants were harvested and then and analyzed to evaluate growth factors, microbiological variables, soil pH, shoot-root and sodium/potassium ratios and mineral nutrient content (N, P. Ca, Mg, Na and Cl). Salinity decreased growth and plant biomass of non-mycorrhizal fertilized plants. Inoculation with AMF increased plant dry matter production when compared with non-inoculated plants under salt stress. When compared with non-fertilized plants, organic compost fertilization increased plant growth, Nutrient contents were always much higher in inoculated plants and in organic compost fertilized plants.